AVALIAÇÃO DA ADIÇÃO DE COLÁGENO HIDROLISADO, AMIDO MODIFICADO E GOMA GUAR EM PRESUNTO COZIDO DE PERU - Prestes, Rosa Cristina (2008)
The main problems observed in cooked hams are bad sliceability and excessive fluids loss after cooking (purge). To reduce these problems the industry uses non-meat ingredients (proteins, polysaccharides and their interactions), but under Brazilian law, it is not allowed to add starch or modified starch in hams. In the present work three ingredients were tested: Firm Tex modified starch (0 to 2%), Grindsted Guar 178-B gum guar (0 to 0.30%) and Collagel hydrolyzed collagen (0 to 2%), following a 2 factorial design with central point. The ingredients addition changed physical characteristics and centesimal composition of the products. There was no significant difference in pH and water activity (Aw). The results showed that for losses (by cooling, freeze-thawing and cooking) the formulations with modified starch presented lower values, indicating the ability of this ingredient to retain water in the product. It seems appropriate to propose the legal permission of starch in ham or the creation of a new class of product in which starch addition would be allowed. The guar gum produced low resistance to cooking however in losses by cooling the results were adequate. The hydrolyzed collagen tested did not give satisfactory results, showing low acceptance due to formation of gel in the ham and losses higher than that of the other ingredients tested. The developed products were considered equal to the commercial product in relation to the texture (p 0.05). In assessing overall quality, the formulation F6 (2% of modified starch) was the one with the best acceptance as detected by the tasters.